Custom in the Present International Law of the Sea - Mik, Cezary (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The study of custom in the modern law of the sea is divided into two parts. The first one will cover both introductory and general issues. First, the framework for analyses will be defined. It will be designated by the concept of international law of the sea on the one hand, and the understanding of customary law in relation to the law of the sea on the other. Next, the relationship between customary law and treaties will be considered, followed by contemporary criticism of customary law and its regulatory capacities.The second part will examine the following issues: 1) the importance of codification of the law of the sea for customary law of the sea; 2) the validity of the law of the sea treaty rules as customary rules of the law of the sea; 3) the development of customary rules under the provisions of the law of the sea treaties; 4) the importance of references to customary rules in provisions of the law of the sea treaties; 5) the issue of conflict of treaty and customary rules of the law of the sea; 6) the importance of customary law of the sea in the development of the law of the sea in areas not regulated by the law of the sea treaties and in new areas of the law of the sea.
Keywords: zwyczaj; międzynarodowe prawo morza; kodyfikacja